International Law Enforcement Against Immigrant Smuggling in Indonesian Waters - Muhamad Furqon Juanda; Amiludin Amiludin; Dwi Nur Fauziah Ahmad (DE LEGA LATA: JURNAL ILMU HUKUM, 2023)
Indonesia, which is in the middle of the world, could become a place where transnational crime, in this case human smuggling, takes place. With this position, Indonesia could become a place where illegal immigrants or people who are being smuggled end up. A systematic literature review (SLR) will be used to gather data to figure out what the problems are in this study. Systematic Literature Review (SLR) is the process of finding, choosing, and critically evaluating research results to answer well-formed questions. One way to deal with the problem of people sneaking into Indonesian waters is through international law enforcement. Because international law enforcement can protect the human rights of people who are smuggling immigrants, it can also keep Indonesian waters safe and secure. Indonesia is working through domestic legislation to address the problem of people smuggling. The effort consists of two parts, namely, prevention efforts and repressive efforts. The Indonesian government should play a more active role in dealing with illegal immigrants through the Directorate General of Immigration and not just passively wait for UNHCR and IOM.